The secret of dry hopped beers – review - Lukáš Jelínek; Jana Müllerová; Marcel Karabín; Pavel Dostálek (Kvasný průmysl, 2018)
Dry hopped beers gain their characteristic flavour from hop products purposely added during the cold stage of production. Although the production of these beers has not so broad a tradition in the Czech Republic as for instant in Great Britain or the United States, their popularity increases every year. This study provides a complete set of theoretical and practical information about the production of dry hopped beers. The relevant sensory active compounds of hops creating the characteristic beer aroma and factors influencing their transfer into beer are introduced. The last part of the study deals with some important risk factors which must be considered during the production of dry hopped beers.